DETEKSI FENOTIPIK Methicillin Resistant Staphylococcus aureus (MRSA) PADA SAMPEL MAKANAN DI SIDOARJO - Yulianto Ade Prasetya (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2019)
Methicillin-resistant Staphyloccocus aureus (MRSA) is an isolate that is resistant to the antibiotic methicillin and beta lactam group. The incidence of MRSA associated with nosocomial infections in various parts of the world is very high, but research on its spread in community infections is rarely reported. This study aims to detect the presence of phenotypic MRSA in food samples in Sidoarjo. The food samples (cilok, fried foods and tempura) collected were then weighed, diluted, and cultured in a selective medium and differential namely Manitol Salt agar. The yellow-colored colonies were then continued with microscopic testing and biochemical tests to distinguish between Staphylococcus species. Thirty eight collected Staphyloccus aureus isolates were then screened using Oxacillin 1 µg and there were eight (8) isolates that were positive for MRSA according to the criteria of the Clinical Laboratory Standart Institutre (CLSI). Eight of the isolates were tested for antibiotic sensitivity with the Kirby-Bauer method with Chloramphenicol 30 µg and Cotrimoxazole 25 µg. Eight MRSA (21%) isolates were resistant to Chloramphenicol and only four isolates were resistant to Cotrimoxazole. The presence of MRSA isolates in community infections needs to be watched out for considering these genes can be transmitted and spread between bacterial species